Self Injury Pengaruh E-Tebu Pro (Edukasi Terapi Butterfly Hug dan Progressive Muscle Relaxation) Terhadap Ekspektansi Self-Injury pada Siswa SMK HKTI 1 Purwareja Klampok - Azzahra, Siti Fatimah; Estria, Suci Ratna; Isnaini, Nur; Lazulfa, Indana (Dinasti Research, 2025)
Self-injury expectancy are a type of violent behavior as a way to vent emotions, where the goal of the self-injury actions is only to injure himself in order to channel his emotions, not to end his life. Butterfly Hug relaxation therapy and Progressive Muscle Relaxation are the therapies used for intervention in this research which have the benefit of stabilizing emotions, reducing tension in the body's muscles and relaxing the body more. The purpose of this study was to determine the effect of Butterfly Hug and Progressive Muscle Relaxation relaxation therapy on self-injury expectancy in SMK HKTI 1 Purwareja Klampok students. The method used in this study used a quantitative pre-experimental one grup research method using a pretest-posttest design with a total sampling of 65 respondents with several predetermined criteria. The results showed that there was a difference before and after the intervention was given with an average score, before the intervention was 70.20 and after the intervention increased to 53.40 using the Kolmogorov-Smirnov test (respondents 65) and the p-value was 0.80 so it can be concluded that the data is normally distributed. In addition, a paired t-test has been conducted showing the effect of butterfly hug and progressive muscle relaxation therapy on nonsuicidal self-injurybehavior with a p-value of 0.001 where this value is less than <0.05. In this study, butterfly hug and progressive muscle relaxation therapy have an effect on overcoming self-injuryin vocational high school students who experience self-injurybehavior. Through this technique, students can channel pent-up emotions that result in self-injurybehavior, so that they can stabilize their emotions again.